2018
DOI: 10.1111/ijpo.12464
|View full text |Cite
|
Sign up to set email alerts
|

An addiction model‐based mobile health weight loss intervention in adolescents with obesity

Abstract: SummaryBackground: Clinical approaches to treating childhood obesity can be expensive and poorly reimbursed, and often produce suboptimal results. It has been theorized that overeating may have addictive qualities, and a sizable number of adolescents with obesity endorse addictive habits. Interestingly, few weight management interventions have tested techniques founded in addiction medicine principles. We therefore performed a pilot study of an addiction model based mHealth weight loss intervention in adolesce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
127
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(152 citation statements)
references
References 29 publications
1
127
2
Order By: Relevance
“…Three studies (Mameli et al, ; Nguyen et al, ; Vidmar et al, ) evaluated the effects of mobile phone intervention on changes in body weight, and all studies were included for the meta‐analysis (Figure ). On pooling data from three studies, the results favored mobile phone interventions; however, the results were not statistically significant (SMD = −0.043, 95% CI = −0.322 to 0.236).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Three studies (Mameli et al, ; Nguyen et al, ; Vidmar et al, ) evaluated the effects of mobile phone intervention on changes in body weight, and all studies were included for the meta‐analysis (Figure ). On pooling data from three studies, the results favored mobile phone interventions; however, the results were not statistically significant (SMD = −0.043, 95% CI = −0.322 to 0.236).…”
Section: Resultsmentioning
confidence: 99%
“…Proper application of health behavior theories and intervention strategies tailored to specific population groups may produce optimal outcomes (Nightingale et al, ; Schoeppe et al, ). Furthermore, although mobile phone interventions are cost‐effective, only one of the included studies (Vidmar et al, ) conducted an economic evaluation. However, the economic benefits of mobile phone interventions are not confirmed due to lack of evidence, thereby hindering the broader application (Badawy & Kuhns, ; Iribarren, Cato, Falzon, & Stone, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, there have been recommendations for interventions among adolescents that promote executive functioning in the context of salience and reward processing [ 196 ]. Among adolescents with obesity ( n = 18), an FA-informed mobile health (app) intervention reduced zBMI in a more cost-effective manner than the in-clinic intervention, and there is currently an RCT underway in a larger sample using this approach [ 229 , 230 ]. It has been suggested that the more interactive, engaging and person centered a mobile health treatment is, the more appealing it will be to those suffering from compulsive overeating [ 231 ].…”
Section: Interventions For Food Addictionmentioning
confidence: 99%
“…Some evidence supports the use of telehealth or mobile health interventions as an adjunct to pediatric weight management as feasible and cost-effective, 8,9 but little data exists on the efficacy or effectiveness of exclusive telehealth for pediatric weight management. In the time of COVID-19 closures and physical distancing, telehealth has become a necessary default.…”
Section: Accepted Articlementioning
confidence: 99%